2020
DOI: 10.1080/10242694.2020.1733896
|View full text |Cite
|
Sign up to set email alerts
|

Affordability Aspects in the Development of Defence Equipment: Case Studies of Concept Generation in the Defence Industry

Abstract: Cost escalation for many complex defence equipment is arguably not sustainable. Customer driven requirements have led to an exponential increase in costs by pushing frontiers of technology to support primarily incremental improvements of traditional equipment concepts. Accordingly, affordability has become a more discussed subject in defence acquisition. This paper addresses the process of generating complex defence equipment concepts. The purpose is to explore how affordability is managed in that process and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Such a system of systems view together with a lifecycle perspective open up for more possibilities to transfer functions and their associated costs (Bobinis and Herald 2012). Accordingly, an expanded tradespace increases the likelihood of identifying other solutions rather than merely replacing an old product concept with a new one of a similar type (Amann, Kihlander, and Magnusson 2020), and can enable cost-effective capabilities (Walden et al 2015). Affordability is thus to be defined from a capability perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a system of systems view together with a lifecycle perspective open up for more possibilities to transfer functions and their associated costs (Bobinis and Herald 2012). Accordingly, an expanded tradespace increases the likelihood of identifying other solutions rather than merely replacing an old product concept with a new one of a similar type (Amann, Kihlander, and Magnusson 2020), and can enable cost-effective capabilities (Walden et al 2015). Affordability is thus to be defined from a capability perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In spite of potential benefits and challenges, affordability management does not surface in recent reviews of CoPS research topics (Ranjbar, Park, and Kiamehr 2018), and it is claimed that there is a lack of attention paid to the way that affordability is taken into account in the early phases of product development (Amann, Kihlander, and Magnusson 2020). The aim of this study is therefore to address this gap in the literature by focusing on affordability management in concept development in order to identify ways to support the development of less costly CoPS without compromising customer needs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in order to overcome design fixation (Jansson and Smith 1991) and the influence of guiding posts (Sahal 1981), it is suggested that it is beneficial to understand the entire capabilities to which specific equipment contribute, for example, air defence, and their cost structures. Such understanding might open up for new combinations with untraditional and affordable solutions (Amann, Kihlander, and Magnusson 2020). Accordingly, management should be active in providing continuous study activities concerning alternative conceptual solutions and potential technologies (Rycroft and Kash 2002).…”
Section: Managing a Path Changementioning
confidence: 99%